Colloquium: The Medieval Countryside in the Aegean and Anatolia: An Archaeological Perspective: Introduction - Athanassopoulos, Effie (Journal of Greek Archaeology, 2021)
This volume brings together papers from the colloquium ‘The Medieval Countryside: An Archaeological Perspective,’ which was originally scheduled to take place in the Archaeological Institute of America (AIA) Annual Meetings, in 2018, in Boston, MA. That year, a blizzard caused massive travel disruptions and led to the cancellation of the colloquium, since most of the participants could not make it to the meetings. Fortunately, it was included in next year’s program, in 2019, when the AIA Meetings were held in San Diego, CA. The Medieval and Post-Medieval Archaeology AIA Interest Group sponsored the colloquium. Five of the papers in this special section were presented at the colloquium. Three additional contributions have been included in order to broaden the geographical coverage and scope of this effort.